An anti-aging reinforced modified abs material for automotive parts
Patent Information
- Application Number
- CN202610834977.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-10
- Publication Date
- 2026-10-27
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, and in particular to an anti-aging reinforced modified ABS material for automotive parts. Background Technology
[0002] ABS resin possesses good impact resistance, high modulus, and excellent processing flow and surface gloss, making it a commonly used thermoplastic engineering plastic in the automotive industry. In recent years, with the development of intelligent connected and autonomous driving technologies, sensors such as LiDAR, millimeter-wave radar, and cameras have been increasingly installed on the exterior of automobiles. ABS resin and its modified materials are also used to manufacture protective housings and structural supports for these sensors.
[0003] Because ABS molecules contain a butadiene rubber phase, their residual unsaturated double bonds are highly sensitive to light, heat, and oxygen. When sensor housings are exposed to ultraviolet radiation and large temperature differences for extended periods, the ABS substrate undergoes photo-oxidation and thermo-oxidative aging, resulting in macroscopic manifestations such as yellowing, chalking, cracking, and decreased light or wave transmission. The resulting microcracks can also allow moisture to penetrate, affecting the sensor's detection accuracy and consequently impacting driving safety.
[0004] Currently, the commonly used anti-aging modification method in industry involves adding small-molecule hindered phenolic antioxidants, phosphite auxiliary antioxidants, and hindered amine light stabilizers to ABS through physical blending. This method has some inherent drawbacks: the small-molecule stabilizers differ significantly from the ABS matrix in polarity and molecular weight, resulting in limited compatibility. Under high and low temperature cycling and outdoor exposure conditions, they are prone to volatilization and migration to the material surface. These volatiles may condense on the surface of optical lenses or waveguides inside sensors, forming a fogging phenomenon, leading to decreased optical performance or signal attenuation. Furthermore, stabilizer loss can cause the housing material to become brittle and fracture more quickly in the later stages of use due to a lack of effective protection.
[0005] To meet the rigidity and strength requirements of sensor protective components, inorganic fillers (such as zinc oxide and calcium carbonate) are typically added to ABS for reinforcement. However, traditional inorganic fillers have high surface energy and weak interfacial bonding with the organic resin matrix. Interfacial defects caused by poor compatibility often become channels for oxygen permeation and initiation points for photo-oxidation reactions, causing the reinforcing filler to accelerate material aging to some extent. In addition, existing compound systems often simply stack antioxidants and light stabilizers as independent components, lacking molecular-level synergy, making it difficult to effectively inhibit the synergistic free radical damage between thermal oxidation and photo-oxidation.
[0006] Therefore, conventional physically modified ABS is insufficient to meet the requirements for high-end autonomous driving sensor housings. There is a need to develop a modified ABS material that can reduce stabilizer volatilization and migration at the molecular structure level and combine interface reinforcement with anti-aging properties. Summary of the Invention
[0007] To address the technical problems in the prior art, such as the easy migration and loss of stabilizers, the easy aging and failure of reinforced filler interfaces, and the synergistic damage caused by thermo-photoaging, this invention provides an anti-aging reinforced modified ABS material for automotive parts.
[0008] According to a first aspect of the present invention, an anti-aging reinforced modified ABS material for automotive parts is provided. The material comprises an ABS resin matrix, a reactive bifunctional macromolecular stabilizer and a core-shell functionalized nano-zinc oxide dispersed in the ABS resin matrix, and a free radical initiator is added during the reactive blending preparation process to initiate in-situ grafting and copolymerization. The reactive bifunctional macromolecular stabilizer has a polybutadiene backbone, on which hindered phenolic antioxidant groups and hindered amine photostable groups are simultaneously grafted, and unsaturated double bonds capable of reacting with the ABS resin matrix are retained. Polybutadiene is used as the backbone because its structure is similar to the rubber phase (polybutadiene phase) in ABS resin. Based on the principle of similarity compatibility, this facilitates the dispersion of the stabilizer in the matrix and its interpenetration with the rubber. The unsaturated double bonds retained on the backbone enable the stabilizer to graft and bond with the matrix during processing, fixing it on the polymer network, thereby reducing the problem of loss due to migration of traditional small molecule stabilizers. The core-shell structured functionalized nano-zinc oxide is an inorganic core-organic shell structure, comprising a nano-zinc oxide core and an organic polymer shell containing hindered phenolic functional groups coated on the surface of the core. The zinc oxide core can shield ultraviolet light, and the organic shell containing hindered phenols is located at the interface between the filler and the matrix, which can capture free radicals generated near the interface and inhibit the initiation of microcracks at the interface.
[0009] Based on the above technical solution, preferably, the material further includes grafted modified lignin. The grafted modified lignin is prepared by first grafting glycidyl methacrylate (GMA) onto alkali lignin, followed by hindered amination treatment: the epoxy groups in GMA undergo ring-opening addition with the phenolic or alcoholic hydroxyl groups of lignin, introducing methacrylate double bonds onto the lignin skeleton. Subsequently, a portion of these double bonds are combined with a secondary hindered amine compound containing only one active hydrogen atom via an aza-Michael addition reaction, introducing hindered amine photostable groups (using a secondary amine avoids the cross-linking gel caused by primary amines bridging two lignin chains due to the presence of two active hydrogen atoms), while retaining the methacrylate double bonds that can participate in free radical reactions. During the reactive blending process, the retained methacrylate double bonds, under the action of free radical initiators, can undergo free radical copolymerization or addition with the butadiene double bonds in the ABS resin rubber phase and the methacrylate double bonds retained on the reactive bifunctional macromolecular stabilizer. For core-shell structured functionalized nano-zinc oxide, its organic shell is a saturated polymer backbone formed by chain copolymerization of methacryloyloxysilane and methacrylate monomers. It does not contain residual double bonds available for copolymerization. Therefore, it mainly generates macromolecular free radicals by abstracting active hydrogen from the saturated backbone through initiator free radicals, which then couple with the chain free radicals of the above components to join the network. Since lignin, reactive macromolecular stabilizers, and ABS rubber phase all have similar unsaturated double bonds, their reactivity is relatively similar and their compatibility is good. Together with the core-shell particles linked by hydrogen abstraction coupling, they form a covalently cross-linked three-dimensional network in the ABS matrix. The rigid benzene ring structure of lignin itself has both toughening and reinforcing effects, and its phenolic hydroxyl groups also have a certain antioxidant capacity. After the above modification, lignin is not only a bio-based toughening component, but also fixes the hindered amine light-stabilizing groups and phenolic structures in the network in the form of covalent bonds. Together with reactive macromolecular stabilizers and core-shell nano zinc oxide, it forms a multi-level protective structure composed of fillers, macromolecular chains and cross-linked networks.
[0010] More preferably, the number-average molecular weight of the reactive bifunctional macromolecular stabilizer is controlled between 6000 and 12000, and the grafting rate is controlled between 25% and 35%. This molecular weight range is chosen because: if the molecular weight is below 6000, the macromolecular chain is too short, making it difficult to form effective physical entanglement with the ABS matrix, and the extraction resistance is poor; if the molecular weight is above 12000, the melt viscosity is too high, leading to uneven dispersion and affecting processing performance. Controlling the grafting rate at 25%-35% is to balance functionality and reactivity: too low a grafting rate results in insufficient density of anti-aging groups and poor protective effect; too high a grafting rate leads to significant steric hindrance, hindering the participation of the main chain double bonds in subsequent cross-linking and curing reactions. This stabilizer is prepared by free radical graft copolymerization of liquid polybutadiene with hindered phenolic and hindered amine monomers under the action of an initiator. It should be noted that, to avoid the phenolic hydroxyl groups of the hindered phenolic monomers inhibiting polymerization or chain transfer during free radical polymerization, 2,6-di-tert-butyl-substituted hindered phenolic monomers are preferred (their phenolic hydroxyl groups are sterically protected by the tert-butyl group, significantly reducing the tendency for active hydrogen extraction). Alternatively, the phenolic hydroxyl groups can be protected by acetylation or other methods, and then deprotected after polymerization. Simultaneously, considering that the double bonds in the polybutadiene backbone (especially the 1,2-vinyl side groups) are both grafting points and potential crosslinking sites, liquid polybutadiene with a moderate 1,2-vinyl content can be selected. While ensuring sufficient grafting active sites, crosslinking gelation can be suppressed through dilute solution polymerization, controlling the monomer dropping rate, and adding chain transfer agents, keeping the product a soluble viscous liquid. This synthetic route ensures the statistical distribution of functional groups on the backbone, which is beneficial for leveraging the synergistic effect of hindered phenols and hindered amines during aging.
[0011] For the core-shell structured functionalized nano-zinc oxide, the preferred core particle size is 20-50 nanometers, and the thickness of the organic polymer shell is 2-6 nanometers. Controlling the particle size to 20-50 nanometers is because this size range maintains the zinc oxide's ability to shield against ultraviolet light while reducing agglomeration caused by excessively small particle sizes. Controlling the shell thickness to 2-6 nanometers ensures relatively complete coverage of the inorganic surface by the organic layer while maintaining the organic grafting rate at approximately 15%-25%, avoiding agglomeration and increased costs due to excessively thick shells.
[0012] Furthermore, the grafted modified lignin is prepared from alkali lignin, and its hindered amine group content is 1.5-3.0 mmol / g. Alkali lignin is chosen because it is widely available and contains a large number of active hydroxyl groups, which facilitates chemical modification. Controlling the hindered amine group content within the above range is to provide sufficient free radical scavenging sites without significantly damaging the rigidity of the lignin skeleton: too low a content is detrimental to long-term photostability, while too high a content increases the difficulty and cost of modification.
[0013] In terms of specific formulation composition, by weight, this invention preferably includes 100 parts ABS resin, 3-8 parts reactive bifunctional macromolecular stabilizer, 2-6 parts core-shell structured functionalized nano zinc oxide, 5-12 parts grafted modified lignin, and 0.05-0.15 parts free radical initiator added during the reaction blending preparation process (this initiator is basically completely decomposed into free radicals in the high-temperature reaction section to initiate in-situ grafting and copolymerization, so it is mainly limited in the form of process addition). This ratio range has been verified by a large number of rheological and mechanical property experiments: the stabilizer dosage is less than 3 parts, the anti-aging effect is not significant, and more than 8 parts may cause excessive cross-linking, leading to material brittleness; less than 2 parts of nano zinc oxide is insufficient for UV shielding, and more than 6 parts is prone to agglomeration, causing stress concentration; the initiator dosage needs to be strictly controlled, too little will not initiate grafting, and too much will lead to excessive cross-linking or even degradation of the matrix.
[0014] Specifically, regarding the selection of chemical structures, the grafting monomers of the reactive bifunctional macromolecular stabilizers are preferably selected from 3,5-di-tert-butyl-4-hydroxystyrene (providing a hindered phenolic group) and 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine (providing a hindered amine group); the shell monomers of the core-shell functionalized nano-zinc oxide include methyl methacrylate and 3,5-di-tert-butyl-4-hydroxystyrene; and the amination reagent for graft-modified lignin is a secondary hindered amine containing only one active hydrogen (such as 4-methylamino-2,2,6,6-tetramethylpiperidine). The selection of these specific compounds is based on a balance between their reactivity and steric hindrance, ensuring successful grafting at processing temperatures while maintaining structural stability during service.
[0015] In addition, the material may also include auxiliary agents selected from phosphite antioxidants (preferably pentaerythritol diphosphite, 0.2-0.5 parts), thioester antioxidants (preferably dilauryl thiodipropionate, 0.1-0.3 parts), and UV absorber UV-327 (0.3-0.6 parts). Phosphite and thioester antioxidants, as hydroperoxide decomposers, can decompose the hydroperoxides (ROOH) generated during aging into stable alcohols, inhibiting auto-accelerated oxidation; the UV absorber absorbs ultraviolet light and, in combination with nano-zinc oxide, provides protection against ultraviolet radiation of different wavelengths.
[0016] The material of this invention is prepared by reactive blending using a twin-screw extruder, with the reaction zone temperature controlled between 200°C and 220°C. This temperature range is chosen because the initiator used (such as DHBP) decomposes rapidly within this temperature range, generating a sufficient concentration of free radicals. This initiates in-situ grafting and copolymerization reactions between the methacrylate double bonds retained on the reactive macromolecular stabilizer, the methacrylate double bonds on the grafted modified lignin, and the double bonds in the ABS matrix rubber phase. Furthermore, the macromolecular free radicals generated by hydrogen abstraction from the saturated organic shell framework of the core-shell functionalized nano-zinc oxide couple with the aforementioned chain free radicals, thus integrating the core-shell particles into the network. Below 200°C, the initiation efficiency is low, the grafting rate is insufficient, and the stabilizer is not easily and effectively fixed. Above 220°C, the ABS matrix is prone to thermal degradation and discoloration, and excessive cross-linking may cause the melt to lose its fluidity. To ensure the ABS matrix is fully melted and plasticized before entering the reaction zone, the extruder's feeding and melting zones should use the conventional ABS melt processing temperature (approximately 190-210℃). The initiator should not be dry-mixed with the material in the hopper; instead, it should be quantitatively injected into the melt in liquid form after the ABS has melted. This prevents premature decomposition of the initiator in the melting zone, which could lead to excessive local cross-linking. The screw speed should be set to 150-250 rpm, and the material residence time in the reaction zone should be 60-120 seconds. Combined with vacuum devolatilization at -0.08 MPa to -0.095 MPa, this provides shear to renew the reaction interface and promptly removes small molecules generated during the reaction, reducing internal porosity in the product. It should be noted that the system of this invention simultaneously contains reactive macromolecular stabilizers, a core-shell zinc oxide shell, and a large number of unsaturated double bonds on grafted modified lignin that can participate in free radical reactions. These comonomers preferentially and competitively consume the free radicals generated by the decomposition of the initiator, so that the free radicals are mainly used for grafting and coupling reactions between the components. This inhibits the irregular excessive cross-linking or degradation of the ABS rubber phase with a low amount of initiator, avoiding the rubber phase damage and material embrittlement commonly seen when simply adding peroxides. With appropriate initiator dosage and residence time, the stability of the matrix can be maintained while improving interfacial compatibility and toughness.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The beneficial effects of this invention, achieved through the aforementioned molecular design and formulation process, are mainly reflected in the following aspects: First, this invention reduces the migration and loss of anti-aging agents. By introducing a reactive bifunctional macromolecular stabilizer with a polybutadiene backbone, and through in-situ grafting reactions initiated by free radicals during processing, hindered phenolic and hindered amine groups are chemically bonded to the ABS resin molecular chains and filler interfaces, transforming the stabilizer from a free small molecule into a component of the polymer network. Therefore, under high temperature or long-term outdoor use conditions, the migration and volatilization of the stabilizer are significantly reduced, and the weather resistance of the material is superior to that of traditional physical blending systems.
[0018] Secondly, this invention improves the aging resistance at the interface of the reinforcing filler, achieving a balance between mechanical reinforcement and anti-aging properties. By employing core-shell structured functionalized nano-zinc oxide and grafted modified lignin, an interface layer containing active groups is formed between the inorganic filler and the organic matrix. The hindered phenolic shell in the core-shell structure and the hindered amine groups on the lignin are enriched in the interface region. When free radicals are generated at the interface due to stress concentration or oxygen permeation, they can be captured in situ, inhibiting the initiation and propagation of microcracks. After long-term aging, the material exhibits minimal color difference change, and the notched impact strength retention rate can reach over 85%.
[0019] Finally, this invention provides comprehensive protection against thermo-oxidative and photo-oxidative aging. Through covalent bonding between reactive macromolecular stabilizers, core-shell nanoparticles, and grafted modified lignin, a three-dimensional cross-linked network is formed within the material, restricting oxygen diffusion and free radical migration. Simultaneously, the synergistic effects of phosphite decomposing hydrogen peroxide, hindered amine capturing free radicals, and UV absorbers absorbing UV light in the formulation effectively inhibit the photodegradation process induced by thermo-oxidative products. This material is suitable for automotive exterior parts and engine peripheral components used in complex environments with high aging resistance requirements, demonstrating significant application value. Detailed Implementation
[0020] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to specific embodiments. It should be noted that the following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.
[0021] Unless otherwise stated, the specifications and sources of the raw materials used in the embodiments and comparative examples in this specification are as follows: ABS resin: PA-757 grade ABS resin produced by Chi Mei Industrial Co., Ltd. of Taiwan, China, with a butadiene content of about 18% and a melt flow rate (220℃ / 10kg) of 1.8g / 10min.
[0022] Initiator: 2,5-Dimethyl-2,5-bis(tert-butylperoxy)hexane (DHBP), purity ≥90%, AkzoNobel.
[0023] Co-antioxidant 626: Bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, BASF, Irgafos126.
[0024] DLTDP, an auxiliary antioxidant: dilaurate thiodipropionate, Adria (Shanghai) Chemical.
[0025] UV absorber UV-327, BASF, Tinuvin 327.
[0026] Calcium stearate, EBS: Industrial grade, commercially available.
[0027] Preparation of reactive bifunctional macromolecular stabilizers (PBD-g-AO / HALS): Liquid polybutadiene (PBD, purchased from Nippon Soda Co., Ltd., Nisso-PB B series) with a number average molecular weight of approximately 5000 and a high content of 1,2-vinyl structure (approximately 30% 1,2-vinyl content) was dissolved in toluene to prepare a dilute solution with a mass concentration of approximately 20% to reduce the risk of gelation. To avoid the inhibitory effect of phenolic hydroxyl groups on free radical polymerization, the phenolic hydroxyl groups of 3,5-di-tert-butyl-4-hydroxystyrene (DBHS, also known as 2,6-di-tert-butyl-4-vinylphenol, CAS No. 19263-36-6, purchased from Shanghai Xinfan Biotechnology Co., Ltd., purity ≥97%; this monomer is not a conventional commercial product and can also be obtained by decarboxylation of 3,5-di-tert-butyl-4-hydroxycinnamic acid in aprotic polar solvents such as dimethyl sulfoxide at temperatures below 150°C) were acetylated with acetic anhydride to obtain an acetylated hindered phenolic monomer. Add 50% of the PBD mass of the mixed monomers, which consist of the above-mentioned acetoxylated hindered phenol monomer and 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine (TMPM, also known as 2,2,6,6-tetramethylpiperidine-4-ylmethacrylate, CAS No. 31582-45-3, purchased from Bidepharm, purity 98%; this monomer is not a conventional commercial product and can also be prepared by esterification of 2,2,6,6-tetramethyl-4-piperidinol with methacryloyl chloride or methacrylic anhydride) in a molar ratio of 1:1. Add 2.0% of the total monomer mass of benzoyl peroxide (BPO), and add the monomers dropwise at 85°C under nitrogen protection and react for 12 hours. In this grafting system, the selected styrene-type and methacrylate-type monomers exhibit high reactivity. Their growing chain radicals can add to the double bonds (including the 1,2-vinyl side groups) of the polybutadiene backbone to form grafting sites. Simultaneously, the BPO primary radicals can also abstract allyl hydrogen from the backbone to assist in initiating grafting. To suppress gelation caused by crosslinking of the backbone double bonds and homopolymerization side reactions, a small amount of dodecyl mercaptan (0.5% of the total monomer mass) is added as a chain transfer agent during the reaction. Grafting efficiency is improved and the proportion of free homopolymer is reduced by using dilute solutions, temperature-controlled dropwise addition, and a moderate excess of monomer. After the reaction, a catalytic amount of weak base (such as potassium carbonate / methanol) is added and the mixture is stirred at 25-40℃ for 0.5-2 hours to selectively hydrolyze acetyl groups to deprotect and restore phenolic hydroxyl groups, while avoiding transesterification or hydrolysis of the methacrylate bonds. Subsequently, the solvent and unreacted monomers are removed by vacuum distillation to obtain a pale yellow viscous product (liquid).It should be noted that this process mainly reduces the proportion of free homopolymers at the source by measures such as dilute solution polymerization, controlling the monomer drop rate, and maintaining a moderate excess of double bonds in the main chain. Since the polybutadiene main chain of the grafted product and the free hindered phenol / hindered amine functional monomer homopolymers have similar solubility in common solvents, it is difficult to achieve selective fractional precipitation using a single non-solvent (such as methanol). If necessary, solvents such as acetonitrile, which have weak solubility for non-polar polybutadiene grafts but relatively strong solubility for polar functional monomer oligomers, can be used for extraction to further reduce the content of free homopolymers. GPC analysis showed that the purified product had a number-average molecular weight of 7200 and no insoluble gel. Infrared spectroscopy and titration analysis revealed a grafting rate (defined as the ratio of the total mass of the grafted functional monomer side chains to the mass of the polybutadiene backbone) of 28%, with a total functional group content of approximately 0.96 mmol / g (including approximately 0.48 mmol / g of hindered phenolic groups and approximately 0.48 mmol / g of hindered amine groups), and a retained double bond content of approximately 13 mmol / g. These values corroborate each other: grafting hindered phenolic monomers (approximately 232 g / mol after deprotection) and hindered amine monomers (approximately 225 g / mol) at a 1:1 ratio yields an average unit mass of approximately 228 g / mol. The 0.96 mmol / g functional group corresponds to approximately 0.22 g of grafted side chain mass per gram of product and approximately 0.78 g of backbone mass per gram of product, resulting in a ratio of approximately 28%.
[0028] Preparation of core-shell structured functionalized nano-zinc oxide (ZnO@PMMA-AO): Nano-sized zinc oxide (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) with an average particle size of approximately 30 nm was dispersed in an ethanol / water (volume ratio 9:1) mixed solvent. γ-methacryloyloxypropyltrimethoxysilane (KH-570, 5% of the ZnO mass) was added, and the mixture was stirred at 60°C for 2 hours. This allowed the silane to hydrolyze and condense on the zinc oxide surface, introducing polymerizable methacryloyloxy groups. After centrifugation, washing, and drying, methacryloyloxylated zinc oxide (ZnO-MPS) was obtained. KH-570 was chosen instead of vinyltriethoxysilane because its methacryloyloxy groups have a similar polymerization reactivity with acrylate monomers, allowing for effective copolymerization with shell monomers to form a covalently bonded in-situ polymerized coating layer on the zinc oxide surface. ZnO-MPS was dispersed in toluene to prepare a dispersion with a ZnO mass concentration of approximately 10% (i.e., the amount of toluene was approximately 10 times the mass of ZnO). Methyl methacrylate (MMA) and acetylated protected 3,5-di-tert-butyl-4-hydroxystyrene (DBHS) (molar ratio 5:1) were added, with the total monomer content being 20% of the ZnO mass. Initiator AIBN (1.5% of the total monomer mass) was added, and polymerization was carried out at 70°C for 6 hours, allowing MMA, hindered phenolic monomers, and surface methacryloyloxy groups to copolymerize and graft an organic shell onto the core surface. After polymerization, potassium carbonate / methanol was added and treated at 25-40°C for 0.5-2 hours for alkaline hydrolysis, selectively removing acetylation protecting groups, restoring phenolic hydroxyl groups, and preventing significant saponification of the shell methacrylate. The product was centrifuged, washed, and dried to obtain ZnO@PMMA-AO. Transmission electron microscopy showed a shell thickness of approximately 3-4 nm, and thermogravimetric analysis indicated an organic coating content of 18.5%.
[0029] Preparation of graft-modified lignin (EAL): Alkali lignin (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) was dissolved in DMSO, and glycidyl methacrylate (GMA, with a molar ratio of approximately 1.2:1 to the lignin hydroxyl groups) and tetrabutylammonium bromide catalyst (5% of the mass of alkali lignin) were added. Hydroquinone-based polymerization inhibitors (such as p-methoxyphenol, 0.1% of the mass of GMA) were also added to inhibit the thermally initiated self-polymerization of the methacrylate double bonds during heating. The reaction was stirred at 85°C for 6 hours, allowing the epoxy groups of GMA to undergo ring-opening addition with the phenolic and alcoholic hydroxyl groups of lignin, introducing methacrylate double bonds into the lignin backbone to obtain methacrylated lignin. The epoxy-hydroxyl ring-opening addition can proceed smoothly at this temperature under the catalysis of tetrabutylammonium bromide; the lower reaction temperature combined with the polymerization inhibitor effectively prevents double bond cross-linking and gelation. After the reaction was completed, the reaction solution was slowly added dropwise to a large amount of deionized water to precipitate the methacrylated lignin. After filtration and repeated washing with deionized water to remove residual DMSO, tetrabutylammonium bromide catalyst and unreacted GMA, the product was dried under vacuum at 40°C to obtain a solid intermediate product. The dried methacrylated lignin was redissolved in DMSO, and a secondary hindered amine monomer containing only one active hydrogen, 4-methylamino-2,2,6,6-tetramethylpiperidine (CAS No. 62995-79-3, purchased from J&K Scientific; this reagent is not a conventional commercial product, but can also be prepared by reductive amination or selective monomethylation of 4-amino-2,2,6,6-tetramethylpiperidine) (molar ratio of 4-amino-2,2,6,6-tetramethylpiperidine to methacrylate double bonds approximately 0.7:1) and a catalytic amount of organic base catalyst (such as 1,8-diazabicyclo[5.4.0]undec-7-ene, DBU, at 1% of the total mass of the reactants) were added. The reaction was carried out at 60°C for 8 hours, allowing some of the methacrylate double bonds to undergo a aza-Michael addition reaction with the nitrogen and hydrogen of the secondary amine, introducing hindered amine groups. Secondary amines were chosen instead of primary amines because primary amines contain two active hydrogens, and the secondary amines formed from their initial Michael addition still exhibit nucleophilicity, readily undergoing a second addition with the methacrylate double bond on another lignin molecule chain, thus acting as cross-linking sites and leading to irreversible cross-linking and gelation of the multibranched lignin. 4-Methylamino-2,2,6,6-tetramethylpiperidine, containing only a single active hydrogen, was used. Each amine can only add to one double bond, mechanistically avoiding cross-linking caused by amine bridging. This ensures that the modified lignin maintains its soluble branched structure and retains the methacrylate double bonds that can participate in subsequent free radical reactions. The product, after precipitation, washing, and drying, yielded graft-modified lignin (EAL). Analysis showed that its hindered amine group content was approximately 1.5 mmol / g, and it retained approximately 0.9 mmol / g of methacrylate double bonds that can participate in free radical reactions (consistent with an amine / double bond feed ratio of approximately 0.7:1 and the reaction characteristics of this secondary amine, which involves a single active hydrogen and a single addition).
[0030] Performance testing standards and methods Notched impact strength: Tested according to GB / T1843 standard, with type A notch on the specimen and test temperature of 23℃.
[0031] Tensile strength: Tested according to GB / T1040 standard, tensile rate 50mm / min.
[0032] Flexural modulus: Tested according to GB / T9341 standard, test speed 2mm / min.
[0033] Artificial accelerated aging test (xenon lamp aging): An AtlasCi4000 xenon lamp aging test chamber was used according to GB / T16422.2 standard. Black panel temperature: 65℃; irradiance: 0.51W / m². 2 @340nm, relative humidity 50%, continuous light exposure. Performance was tested after 500 hours and 1000 hours of aging.
[0034] Yellowing index (ΔYI): The change in yellowing index before and after aging is measured using a colorimeter.
[0035] Stabilizer migration: The prepared standard sample was placed in a Soxhlet extractor and refluxed with anhydrous ethanol for 24 hours. After concentration, the content of specific antioxidant groups (hindered phenols / hindered amines) was determined by HPLC, and the percentage (migration rate) relative to the initial addition amount was calculated.
[0036] Examples 1-6
[0037] According to the formulation ratio (parts by weight) shown in Table 1, the dried ABS resin, PBD-g-AO / HALS, ZnO@PMMA-AO, EAL, and other additives (excluding initiator DHBP) were added to a high-speed mixer. The reactive bifunctional macromolecular stabilizer (viscous liquid) was preheated to 60°C to reduce viscosity and then evenly sprayed onto the high-speed stirred material using a spray device. The mixture was thoroughly mixed to obtain a premix without the initiator. This premix was then added to a co-rotating twin-screw extruder for reactive extrusion. The initiator DHBP was not added dry in the hopper but instead injected laterally in liquid form in the reaction section as described below.
[0038] Extruder process parameters: screw speed 200 rpm; zone temperatures: feeding section 190℃, compression section (melt plasticizing section) 205℃, third zone (melt homogenization section) 210℃, reaction section (fourth and fifth zones) 205-215℃, metering section 210℃, die head 205℃. Considering that the ABS (Chimei PA-757, melt flow rate approximately 1.8 g / 10 min) selected in this invention is a high molecular weight, low flowability extrusion / injection molding grade resin, its effective melt plasticization needs to be carried out at approximately 200℃ or higher. Therefore, the feeding section to the third zone adopts the conventional ABS melt processing temperature, so that the material is fully melted and homogenized before entering the reaction section; at this time, the premix in the hopper does not contain the initiator DHBP, and there is no problem of premature decomposition of the initiator in the low-temperature section. After the ABS is completely melted and plasticized in the third zone, the initiator DHBP (which can be pre-dissolved in a small amount of inert solvent or a portion of liquid macromolecular stabilizer to form an initiator fluid) is quantitatively injected into the melt through a side injection port in the fourth zone (reaction zone) using a metering pump. This concentrates the in-situ grafting and copolymerization reaction in the reaction zone at 205-215℃. Since DHBP has a half-life of only about 1 minute at approximately 181℃, placing its injection point in the melt zone already heated to the reaction temperature allows for rapid and concentrated release of free radicals in the reaction zone. This avoids the sudden increase in torque or screw seizure caused by premature crosslinking in the melting and plasticizing zone, while ensuring a sufficient degree of grafting reaction. The reaction zone is equipped with a vacuum devolatilization port with a vacuum degree of -0.09 MPa. The extruded strip is water-cooled, pelletized, and injection-molded into standard test specimens.
[0039] Table 1: Formulation composition of the examples (parts by weight) Note: Example 1 is the basic preferred formulation; Example 2 examines the effect of high content macromolecular stabilizer; Example 3 examines the effect of high content core-shell zinc oxide; Example 4 examines the effect of high content modified lignin; Example 5 is a low content cost-type formulation; Example 6 is a comprehensive enhancement formulation.
[0040] Comparative Example To verify the key functions of the various technical features of this invention, the following comparative examples were set up. The preparation process was the same as in Example 1, only the formulation was adjusted.
[0041] Comparative Example 1: Without the self-made components of this invention. Equal amounts of ordinary liquid polybutadiene (ungrafted), commercially available nano zinc oxide (core-shell structure-free), and ordinary alkali lignin (unmodified) were used. Anti-aging agents were directly added using commercially available antioxidant 1010 (0.5 parts), antioxidant 168 (1.0 part), and light stabilizer 770 (0.5 parts).
[0042] Comparative Example 2: The same amount of PBD-g-AO / HALS as in Example 1 was used, but without the initiator DHBP, and the extrusion temperature was reduced to 190°C so that the system did not undergo crosslinking reaction and was only physically dispersed.
[0043] Comparative Example 3: Ordinary nano-zinc oxide was used instead of ZnO@PMMA-AO, and other components were the same as in Example 1. The importance of the interfacial layer for anti-aging was investigated.
[0044] Comparative Example 4: Without EAL, the amount of ABS resin was increased to maintain the overall balance of the formulation, and other components were adjusted proportionally. The toughening and anti-aging effects of the lignin system were investigated.
[0045] The performance test results of each embodiment and comparative example are summarized in Table 2.
[0046] Table 2: Test Results of Physical and Mechanical Properties and Aging Performance 1. The decisive role of stabilizers in fixation (Example 1 vs. Comparative Examples 1 & 2): Comparative Example 1 represents the mainstream physical blending technology currently on the market. After aging for 1000 hours, its impact strength retention rate was only 42%, and the surface showed severe yellowing (ΔYI as high as 12.8). This is because the small molecule stabilizer has a migration rate as high as 45.6%, and a large amount is lost during the aging process.
[0047] Although Comparative Example 2 used a macromolecular stabilizer, it did not add an initiator for chemical initiation (no DHBP). Its migration rate (9.5%) was significantly lower than that of Comparative Example 1, but still significantly higher than that of Example 1 (1.5%). It should be noted that the migration rate in this invention is the percentage of extracted functional groups relative to the initial amount after Soxhlet reflux extraction with anhydrous ethanol for 24 hours, determined by HPLC. It reflects the extractable portion of the solvent rather than simply the loss due to thermal volatilization. The macromolecular stabilizer used in Comparative Example 2 has a number-average molecular weight of approximately 7200 and is an elastomeric oligomer with a very low glass transition temperature, mainly composed of 1,2-vinyl groups. In the non-polar ABS matrix, it exists only in a physically dispersed form. Under long-term ethanol reflux extraction, the lower molecular weight fractions and end segments of this type of oligomer, which are not chemically bonded and have limited compatibility, are still gradually dissolved by the solvent, thus exhibiting an extractable migration rate of approximately 9.5%. This does not contradict its large molecular weight and its characteristic of not easily volatilizing and losing large amounts of molecules like small molecule additives. In contrast, in the examples where DHBP-initiated grafting of the PBD-g-AO / HALS main chain double bonds to the matrix resulted in the stabilizer becoming part of the polymer network, significantly improving extraction resistance and reducing migration to 1.5%. This indicates that DHBP-initiated grafting of the main chain double bonds to the matrix is key to reducing stabilizer migration. The lower migration rates of Examples 1-6 correspond to their higher performance retention after aging (greater than 85%).
[0048] 2. Synergistic effect of interface anti-aging and enhancement (Example 1 vs. Comparative Example 3): The difference between Example 1 and Comparative Example 3 lies in whether the zinc oxide possesses a core-shell structure containing hindered phenols. Data shows that Comparative Example 3 exhibits a lower initial impact strength (15.8 kJ / m). 2 vs 22.4kJ / m 2 Furthermore, the performance of ordinary nano-zinc oxide deteriorates rapidly after aging. This is because the bonding between ordinary nano-zinc oxide and ABS is poor, and the interface is also a region where photo-oxidation reactions are more likely to occur. The ZnO@PMMA-AO of this invention forms a chemically bonded transition layer at the interface through the hindered phenolic groups in the shell, which not only improves the toughening effect of the initial interface, but also inhibits the propagation of interfacial microcracks during aging, thereby improving the toughness retention rate after aging.
[0049] 3. Toughening and Anti-aging Aid of Lignin (Example 1 vs. Comparative Example 4): Comparing Example 1 and Comparative Example 4 (without EAL), it can be seen that after removing the grafted lignin, the initial impact strength of the material decreased from 22.4 kJ / m² to 14.2 kJ / m². 2This indicates that EAL, as a bio-based toughening component, plays a significant toughening role. Meanwhile, the aging performance of Comparative Example 4 also decreased (retention rate 72.1%), confirming that the hindered amines grafted onto EAL and the phenolic hydroxyl groups of lignin itself participate in the anti-aging synergistic network, playing a supplementary protective role.
[0050] 4. The influence of formulation gradient: Example 2 increased the amount of macromolecular stabilizer, resulting in the highest aging retention rate (94.2%) and the lowest yellowing, indicating that the increased density of anti-aging groups helps improve weather resistance without significantly impairing mechanical properties, thus confirming the good compatibility between the PBD backbone and ABS.
[0051] Example 3 increased the amount of core-shell zinc oxide, which significantly improved the flexural modulus (rigidity) (2620MPa), but the impact strength decreased slightly, which is in line with the general rule of rigid particle filling. However, thanks to the core-shell structure, the decrease was much smaller than that of traditional filling modification.
[0052] Example 4 increased the amount of modified lignin, resulting in the highest initial impact strength (24.1 kJ / m). 2 This demonstrates the excellent toughening effect of EAL.
[0053] In summary, this invention mitigates the problems of stabilizer migration and easy aging at the interface in traditional ABS materials through a covalently bonded network between reactive macromolecular stabilizers, functionalized core-shell zinc oxide, and grafted modified lignin. While maintaining high strength and toughness, it improves the long-term anti-aging performance of the material.
[0054] It should be noted that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An anti-aging reinforced modified ABS material for automotive parts, characterized in that, The material comprises an ABS resin matrix, a reactive bifunctional macromolecular stabilizer and a core-shell functionalized nano-zinc oxide dispersed in the ABS resin matrix, and a free radical initiator is added during the reactive blending preparation of the material; by weight, the reactive bifunctional macromolecular stabilizer is 3-8 parts, the core-shell functionalized nano-zinc oxide is 2-6 parts, and the free radical initiator is added in the reactive blending preparation of the material in the amount of 0.05-0.15 parts; The reactive bifunctional macromolecular stabilizer has a polybutadiene backbone, on which hindered phenolic antioxidant groups and hindered amine light-stabilizing groups are simultaneously grafted. The backbone retains unsaturated double bonds that can chemically graft with the ABS resin matrix. The number average molecular weight of the reactive bifunctional macromolecular stabilizer is 6000-12000, and the grafting rate is 25%-35%. The core-shell structured functionalized nano-zinc oxide includes a nano-zinc oxide core and an organic polymer shell coating the surface of the core. The organic polymer shell contains hindered phenolic functional groups. The particle size of the nano-zinc oxide core is 20-50 nanometers, and the thickness of the organic polymer shell is 2-6 nanometers.
2. The anti-aging reinforced modified ABS material according to claim 1, characterized in that, The material also includes graft-modified lignin; the graft-modified lignin is lignin that has been grafted with glycidyl methacrylate and modified by hindered amination. Its molecular structure contains hindered amine groups and methacrylate double bonds that can participate in free radical reactions. The methacrylate double bonds can undergo free radical copolymerization or addition with the ABS resin matrix and reactive bifunctional macromolecular stabilizers under the action of free radical initiators, and couple with macromolecular free radicals generated by hydrogen abstraction from the core-shell structured functionalized nano zinc oxide organic shell, thereby forming chemical bonds.
3. The anti-aging reinforced modified ABS material according to claim 1, characterized in that, The reactive bifunctional macromolecular stabilizer is prepared by free radical graft copolymerization of liquid polybutadiene with hindered phenolic monomers and hindered amine monomers under the action of an initiator.
4. The anti-aging reinforced modified ABS material according to claim 1, characterized in that, The organic polymer shell of the core-shell structured functionalized nano zinc oxide is formed by in-situ polymerization of nano zinc oxide modified with a silane coupling agent containing methacryloyloxy group, methacrylate monomers, and monomers containing hindered phenolic functional groups.
5. The anti-aging reinforced modified ABS material according to claim 2, characterized in that, The grafted modified lignin is prepared by reacting alkali lignin with glycidyl methacrylate, causing the epoxy group of glycidyl methacrylate to undergo ring-opening addition with the hydroxyl group of lignin, introducing a double bond of methacrylate onto the lignin, and then introducing a hindered amine group by reacting it with a secondary hindered amine compound containing only one active hydrogen through an aza-Michael addition reaction; wherein the hindered amine group content of the grafted modified lignin is 1.5-3.0 mmol / g.
6. The anti-aging reinforced modified ABS material according to claim 2, characterized in that, The material comprises, by weight: ABS resin: 100 parts; reactive bifunctional macromolecular stabilizer: 3-8 parts; core-shell structure functionalized nano zinc oxide: 2-6 parts; grafted modified lignin: 5-12 parts; and 0.05-0.15 parts of free radical initiator added during the reactive blending process.
7. The anti-aging reinforced modified ABS material according to claim 6, characterized in that, The grafting monomer of the reactive bifunctional macromolecular stabilizer is selected from 3,5-di-tert-butyl-4-hydroxystyrene and 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine; the shell monomer of the core-shell structured functionalized nano zinc oxide includes methyl methacrylate and 3,5-di-tert-butyl-4-hydroxystyrene; the amination agent of the grafted modified lignin is a secondary hindered amine containing only one active hydrogen, selected from 4-methylamino-2,2,6,6-tetramethylpiperidine and 4-butamino-2,2,6,6-tetramethylpiperidine.
8. The anti-aging reinforced modified ABS material according to claim 6, characterized in that, The material also includes auxiliary agents, which are selected from at least one of phosphite antioxidants, thioester antioxidants, UV-327, and lubricants; the phosphite antioxidant is bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, with an addition amount of 0.2-0.5 parts; the thioester antioxidant is dilauryl thiodipropionate, with an addition amount of 0.1-0.3 parts.
9. The anti-aging reinforced modified ABS material according to any one of claims 1 to 8, characterized in that, The material is prepared by reactive blending using a twin-screw extruder, wherein the temperature of the reaction section of the twin-screw extruder is controlled between 200°C and 220°C.
10. The anti-aging reinforced modified ABS material according to claim 9, characterized in that, The twin-screw extruder has a screw speed of 150-250 rpm, the residence time of the material in the reaction section is controlled at 60-120 seconds, and a vacuum devouring port is provided before the homogenization section of the extrusion process, with the vacuum degree controlled at -0.08MPa to -0.095MPa.